Pengelolaan sumberdaya kelautan dan perikanan berbasis wilayah pengelolaan perikanan (WPP) dengan memanfaatan WebGIS - Ifan R. Suhelmi; Yulius .; Dini Purbani (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2013)
Abstract. Management of marine and fisheries resources should consider the carrying capacity and assimilation capability of marine and fisheries resources. The minister regulation Number 1 year 2009 concerning the division of fisheries management zone into 11 zone (WPP) is an effort in managing of marine and fisheries resources. This study was aimed to: (1) Update base map and information at WPP and (2) Aplication of WebGIS technology to manage marine and fisheries resources. The collection data as spatial database, Geographic Information System was used to analyze the data and the presentation of information as Web GIS format. The Results of this research was data and information associated with fishing management zone (WPP) in the form of spatial database in WebGIS format.Keywords: WPP; Marine and Fisheries Resources; Web GIS